The role of IMRT in reduction of the rectal dose during radiotherapy of prostate cancer - Ziółkowska, Ewa; Reszke, Joanna; Morgaś, Tomasz; Drzewiecka, Barbara; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2005)
Introduction: Several clinical studies revealed that doses higher than 70 Gy may be desirable to improve local control in prostate cancer. Rectal toxicity appears to be most clinically relevant and dose-limiting organ for prostate radiotherapy. The probability of late rectal complications has been reported to increase with larger volumes irradiated to target dose levels – dose-volume effect. Purpose: Treatment plans – 3D-CRT and IMRT – were compared using dose statistics and rectum dose-volume histograms (DVH). Materials and methods: We performed a planning study on the CT data of 30 consecutive patients with localised prostate cancer treated at The Oncology Centre in Bydgoszcz between 2002 and 2003. The target volume and relevant organ at risk were outlined on Eclipse 7.1.67 planning workstation. For each of the patients both 3D-CRT and IMRT plan were created. Treatment plans were created with 15-MV photons, with uniform prescription 78 Gy in 39 fractions to the prostate. Results: Compared with 3D-CRT plans, the mean, modal, maximal, median rectum doses were reduced in IMRT plans (p<0.001). Relative rectal volumes irradiated to greater than 40, 50, 60, 65, 70, 75 Gy were significantly decreased with IMRT (p<0.001). For the rectal volume carried to 30 Gy the difference between both techniques was not statistically significant. Conclusion: These results indicate that 3D-CRT with prescription dose 78 Gy to the prostate, carry rectal volume to high dose levels. IMRT reduced the volumes of rectal volume carried to high dose levels to the safe levels. The PTV homogeneity was significantly higher in the 3D-CRT plans.